Impact of water resources availability on agricultural sustainability in the Gavkhuni river basin, Iran - Salemi, Hamidreza; Mohd Soom, Mohd Amin; Lee, Teang Shui; Yusoff, Mohd Kamil (Universiti Putra Malaysia Press, 2011)
One of the most interesting water management case studies in Iran is the case of Zayandehrud River, the main river that supplies water to Isfahan Province which is located in Gavkhuni River Basin (GRB). This paper examines the present and future demands for water and determines the extent to which water will be available for agricultural use by the year 2020. Although demand and supply conditions in 2000 were more or less in balance, there was an increase in the supply of some 28% by 2010 due to the completion of the third trans-basin diversion and the development of other local water sources. However, the demand exceeded its supply in 2010 and the basin fell into severe deficit. In this condition, the only way to keep supply and demand in balance is to reduce allocations to agriculture. By 2020, agriculture would only have 5% more water than the present and water supply is only 90% that of the normal, and this would then shrink from 2025 onwards. In other words, agriculture would have to be sacrificed in order to ensure full supplies of water for the other sectors. The scenarios examined reveal that a sustainable agriculture can only be accomplished by water saving practices and management measures, which may further lead to reduced demand, control supplies, and improve the efficiency of water use.